Obesity-associated diabetes, the human AMPKgamma3 R225W mutation and skeletal muscle metabolism - Crawford, Sean A (University of Ottawa (Canada), 2009)
The prevalence of obesity and type 2 diabetes mellitus (T2DM) is increasing worldwide at an unprecedented pace. The fundamental understanding of the molecular mechanisms underlying the pathogenesis of these diseases is essential for the development of novel therapeutics. The objective of this work was to characterize skeletal muscle metabolism of obese subjects with a history of T2DM and that of subjects carrying the AMP-activated protein kinase (AMPK) gamma3 R225W mutation. Primary myotubes from obese subjects with a history of T2DM showed defects in mitochondrial biogenesis, oxidative capacity and in mechanisms known to mitigate oxidative stress. Conversely, primary myotubes from subjects carrying the AMPKgamma3 R225W mutation had elevated mitochondrial content and oxidative capacity relative to matched controls. R225W carriers also showed evidence of increased muscle glucose uptake in vivo and in vitro, leading to the conclusion that AMPKgamma3 may represent an effective novel pharmaceutical target for treatment of T2DM.
Keywords: Chemistry, Biochemistry.